МАКТАБГАЧА ТАЪЛИМ ЁШИДАГИ БОЛАЛАРИНИНГ БИЛИШ ФАОЛИЯТИНИ РИВОЖЛАНТИРИШГА ЙЎНАЛТИРИЛГАН ЎҚУВ ВАЗИЯТЛАРИДАН ФОЙДАЛАНИШНИНГ ПЕДАГОГИК ШАРТ-ШАРОИТЛАРИ - Жумашева, Г.; Базарбаева, А. (SCIENCE and SOCIETY, 2022)
The article deals with the problem of independent self-government in certain educational situations, which is a necessary condition for the development of the cognitive activity of children. The article argues that the formation of children as subjects of the educational process requires them to spiritual knowledge. As a result of the systematic involvement of children is achieved in problem situations, a higher level of cognitive activity